INTRODUCTION OF FAMILY-ORIENTED MODEL OF BIRTHRATE GOVERNMENT SUPPORT AS A TOOL TO OVERCOME DEPOPULATION PROCESSES IN UKRAINE - Afanasieva Yu.V. (Pressing Problems of Public Administration, 2016)
The necessity of implementation as well as the essence of family oriented model of state support of birth rate as an instrument to overcome depopulation processes in Ukraine has been grounded. Its components and interrelations between them have been described.